Assessing public and sports policies to tackle match-fixing - Cima, C.; Moriconi, M. (Understanding match-fixing in sport: Theory and practice, 2023)
With the massive growth and spread of the sports betting industry, new structure opportunities and risk areas for match-fixing have emerged, particularly related to the infiltration of organised crime syndicates in sport. In view of the seriousness of the scenario and the inadequacy of existing public and sports policies to combat this “new” threat, sports governance bodies, intergovernmental institutions and national governments have coordinated efforts to reform the current legislative and disciplinary frameworks. The hegemonic solution was the adoption of a “zero-tolerance” policy based on three pillars: prevention (educational programmes), regulation (reform of the legal and regulatory framework) and monitoring (monitoring of sports betting). Using a taxonomic model, this chapter discusses the effectiveness of new public and sports policies to prevent and tackle match-fixing. We seek to understand the extent to which these policies have achieved behavioural changes at the level of three interconnected dimensions: sports betting practices, reporting wrongdoing in sport and manipulation of sport competitions. Since the Portuguese Football Federation has strictly followed the “zero-tolerance” policy and has promoted a new legal framework for combating the phenomenon, we consider Portuguese football as a strategic case to assess the adequacy of these measures.